2018
DOI: 10.1111/ajad.12786
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to extended release naltrexone: Patient and treatment characteristics

Abstract: Results extend the findings of other studies and add to an emerging appreciation of the factors associated with treatment retention for extended release naltrexone. (Am J Addict 2018;27:524-530).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…93,94 Fiveyear outcome data for naltrexone are not available, with most studies focused on data over a 6-month period 57,94,109 with a few studies looking up to a year showing some positive retention in the right populations with the right support. 110,111 Research demonstrated an association of naltrexone injections with long-term recovery among nurses (2 years), but, again, this group was highly motivated, a generally higher socioeconomic status cohort, and heavily involved in a structured professional monitoring program. 112 Given such robust response rates by this nursing cohort, it raises the question why this level of oversight and support is not more broadly used in the treatment community.…”
Section: Preparation/administrationmentioning
confidence: 99%
“…93,94 Fiveyear outcome data for naltrexone are not available, with most studies focused on data over a 6-month period 57,94,109 with a few studies looking up to a year showing some positive retention in the right populations with the right support. 110,111 Research demonstrated an association of naltrexone injections with long-term recovery among nurses (2 years), but, again, this group was highly motivated, a generally higher socioeconomic status cohort, and heavily involved in a structured professional monitoring program. 112 Given such robust response rates by this nursing cohort, it raises the question why this level of oversight and support is not more broadly used in the treatment community.…”
Section: Preparation/administrationmentioning
confidence: 99%
“…The extended‐release form of NTX known as Vivitrol, approved by the FDA in 2010, yields plasma levels of NTX that are sufficient to bind to the mu‐opioid receptors for up to 28 days and can be administered in outpatient clinics. However, a pilot study conducted with Vivitrol showed that 32% of the active study group failed to complete the four monthly injections, highlighting the current problem of patient adherence with monthly injections 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…However, a pilot study conducted with Vivitrol showed that 32% of the active study group failed to complete the four monthly injections, highlighting the current problem of patient adherence with monthly injections. 7,8 Another potential solution to the poor adherence with NTX is an extended-release subcutaneous NTX implant. These implants, if successful, would substantially reduce the patient adherence barrier through longer durations of active medication delivery.…”
mentioning
confidence: 99%